Cooperative Financial Performance Analysis of Liquidity, Solvency, Profitability, and Activity Ratios: (A Case Study of the Tirta Dharma PDAM Cooperative in Samarinda City based on Ministerial Regulation Number 06/Per/M.KUKM/V/2006) - Hamsyah, Hamsyah; Latif, Imam Nazarudin; Dewi, Catur Kumala (PT Global Digital Sains Tekno, 2023)
Cooperatives have an essential role in constructing national economic development, and their financial analysis is needed to evaluate the efficiency of their financial performance. This study aims to evaluate cooperatives' profitability, solvency, liquidity, and activity ratios in the years 2016–2018. The results will be analyzed using trend lines to determine if cooperative financial performance increased or decreased during that time. In this study, researchers employ liquidity ratios, specifically current ratios, as analytical tools. Solvency Ratios consist of Total Debt to Equity Ratio and Total Debt to Assets Ratio. Activity Ratios using ratios—accounts receivable turnover—and Profitability Ratios comprising Economic Profitability, Return on Assets, and Net Profit Margin. The study's findings and the subsequent discussion demonstrate that the results were excellent when the liquidity ratio was calculated using the current ratio from 2016 to 2018. The solvency ratio is excellent based on the Total Debt to Equity Ratio and Total Debt to Assets Ratio. Both the total debt-to-equity ratio and the total debt-to-total assets ratio show annual rises in their trend graphs. Economic profitability, return on assets, and net profit margin are used to calculate the profitability ratio, which yields excellent results. The Receivables Turnover ratio calculates the Activity Ratio, which yields subpar results. This analysis suggests that to raise activity ratios, attention should be paid to asset and operational management solutions that are more effective.